2012
DOI: 10.1007/s13139-012-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Parkinsonism Using Dual-Phase F-18 FP-CIT PET Imaging

Abstract: Purpose Dopamine transporter (DAT) imaging can demonstrate presynaptic dopaminergic neuronal loss in Parkinson's disease (PD). However, differentiating atypical parkinsonism (APD) from PD is often difficult. We investigated the usefulness of dual-phase F-18 FP-CIT positron emission tomography (PET) imaging in the differential diagnosis of parkinsonism. Methods Ninety-eight subjects [five normal, seven druginduced parkinsonism (DIP), five essential tremor (ET), 24 PD, 20 multiple system atrophy-parkinson type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Similar to DAT-SPECT findings, striatal DAT PET studies have also found abnormal uptake in PD, MSA- P , PSP and DLB groups versus controls, whereas normal activity was detected in patients with essential tremor and MSA- C [144, 145]. Using dual-phase 18 F-FP-CIT PET, Jin et al found that visual interpretation of early-phase images (acquired at 5-min) to have a favourable diagnostic potential for distinguishing PD from atypical PS (sensitivity 75.4%, specificity 100%) [144]. Using a recently-developed PET radiotracer, 18 F-(E)-N-(3-iodoprop-2-enyl)-2β-carbofluoroethoxy-3β-(4′-methyl-phenyl)nortropane ( 18 F-FE-PE2I), reduction in DAT in the striatum and SN was replicated in PD patients versus controls.…”
Section: Positron Emission Tomography In Parkinsonian Disordersmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar to DAT-SPECT findings, striatal DAT PET studies have also found abnormal uptake in PD, MSA- P , PSP and DLB groups versus controls, whereas normal activity was detected in patients with essential tremor and MSA- C [144, 145]. Using dual-phase 18 F-FP-CIT PET, Jin et al found that visual interpretation of early-phase images (acquired at 5-min) to have a favourable diagnostic potential for distinguishing PD from atypical PS (sensitivity 75.4%, specificity 100%) [144]. Using a recently-developed PET radiotracer, 18 F-(E)-N-(3-iodoprop-2-enyl)-2β-carbofluoroethoxy-3β-(4′-methyl-phenyl)nortropane ( 18 F-FE-PE2I), reduction in DAT in the striatum and SN was replicated in PD patients versus controls.…”
Section: Positron Emission Tomography In Parkinsonian Disordersmentioning
confidence: 72%
“…In contrast to PD, however, putamen and caudate regions were equally impaired in PSP, and the mean uptakes in these regions among MSA patients were in between that of PD and PSP [141]. Similar to DAT-SPECT findings, striatal DAT PET studies have also found abnormal uptake in PD, MSA- P , PSP and DLB groups versus controls, whereas normal activity was detected in patients with essential tremor and MSA- C [144, 145]. Using dual-phase 18 F-FP-CIT PET, Jin et al found that visual interpretation of early-phase images (acquired at 5-min) to have a favourable diagnostic potential for distinguishing PD from atypical PS (sensitivity 75.4%, specificity 100%) [144].…”
Section: Positron Emission Tomography In Parkinsonian Disordersmentioning
confidence: 91%
“…Three-dimensional (3D) emission PET data were acquired for 10 min as described in detail elsewhere. 21 FPCIT PET images were warped into MNI space using an in-house template 22 and SPM5 software. Regions-of-interest for the putamen, caudate and cerebellum (reference region) are placed on each normalized FPCIT PET image using automated anatomical labeling.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…In this study, we investigated the feasibility of the nigrosome 1 detection at 3T MR imaging for the diagnosis of patients with early-stage IPD with abnormal findings on DAT PET imaging. 12 Additionally, we assessed the agreement of asymmetry between the nigrosome 1 detection and patient symptoms, and the asymmetry between the DAT PET imaging and patient symptoms.…”
mentioning
confidence: 99%